Determining a least-cost routing and MAC strategy for a rural communications Ad hoc Network - Van Ellewee, Stephan (Stellenbosch : University of Stellenbosch, 2008)
Thesis (MScEng (Electrical and Electronic Engineering))--University of Stellenbosch, 2006.